Jan Kempenaers. Picturesque - Kempenaers, Jan; KASK; De Meyer, Dirk (Amsterdam : Roma Publications Amsterdam, 2012)
Many of the works of the Belgian photographer Jan Kempenaers are artistic presentations of fragments of our environment - landscapes, as we have come to call them. Some of these landscapes are "natural" ones and continue an overtly picturesque tradition, like for instance his arresting photographs of rocks and forest landscapes. Others may come across as "natural" but upon close examination they reveal the traces of man's intervention.
boek
Keywords: Kempenaers, Jan